The NIFTY study: A multicentre randomised double‐blind placebo‐controlled trial of nifedipine maintenance tocolysis in fetal fibronectin‐positive women in threatened preterm labour. (8th February 2014) - Parry, Emma; Roos, Carolien; Stone, Peter; Hayward, Lynsey; Mol, Ben Willem; McCowan, Lesley
<x xml:space="preserve">Abstract</x> Objective In an unselected group of women with signs of preterm labour, maintenance tocolysis is not effective in the prevention of preterm birth and does not improve neonatal outcome. Among women with signs of preterm labour, those who are fetal fibronectin positive have an increased risk of preterm birth. We investigated whether maintenance tocolysis with nifedipine would delay delivery and improve neonatal outcome in women with threatened preterm labour and a positive fetal fibronectin status. Study Design Women with a singleton pregnancy in threatened preterm labour (24+0 to 33+6 weeks) with a positive fetal fibronectin test were randomised to nifedipine or placebo. Study medication was continued until 36 completed weeks' gestation. The primary endpoint was prolongation of pregnancy of seven days. Secondary endpoints were gestational age at delivery and length of NICU admission. Results Of the 60 participants, 29 received nifedipine and 31 placebo. Prolongation of pregnancy by >7 days occurred in 22/29 (76%) in the nifedipine group and 25/31 (81%) in the placebo group (relative risks, RR 0.94 [0.72–1.2]). Gestational age at delivery was 36.1 ± 5.1 weeks for nifedipine and 36.8 ± 3.6 weeks for placebo (P = 0.027). Length of NICU admission [median (interquartile ranges, IQR)] was 27 (24–41) days and 16 (8–37) days in nifedipine and placebo groups, respectively (P = 0.17). Conclusion In women with threatened preterm labour who are fetal fibronectin positive, maintenance tocolysis with nifedipine does not seem to prolong pregnancy, nor reduce length of NICU admission.